Analysis of extending days on feed for increased profitability of cattle in Iowa feed lot - Moore, Sean (Kansas State University, 2024)
Feeding cattle in a feed lot for the appropriate number of days is critical to the success of a cattle operation. Changes in starting weight of feeder calf, corn price, packer grids, and live cattle futures prices all impact the profitability of growing a steer from calf to finish. The purpose of this thesis is to analyze historical five area weekly live cattle prices over a 10-year period, as well as build a spreadsheet model that helps to optimize the number of days on feed for cattle to improve livestock enterprise profitability. Historical weekly data was collected, and statistical tests were performed to determine if there is significant differences in select target weeks over time to assess if revenue gains can be made by feeding longer. A spreadsheet model was then built to incorporate live cattle futures markets, average daily gain, dressing percentage, and packer grids to assess targeted days on feed for cattle to aid in the decision-making process of what the most desirable number of days on feed is for a given year to help optimize livestock returns. Sensitivity analyses were performed to determine what effects corn price fluctuations would have on overall net returns at predetermined days on feed. Sensitivity analysis on December live cattle futures was also completed to determine at what point extended days on feed result in higher returns. The results of this model are of interest to medium-sized privately owned feedlots that are looking to determine what weight they should buy feeder calves at and for how long they should feed them.
Keywords: Cattle; Days on feed; Live cattle prices; Average daily gain; Extend days on feed; Profitibility